“EMPATHY HAS BIOLOGICAL FOUNDATIONS, BUT CULTURE DETERMINES WHO WILL BE THE SUBJECT OF THAT IDENTIFICATION” - Lynn Hunt; Cilza Bignotto; Carlos cortez Minchillo (Revista Brasileira de Literatura Comparada, 2024)
Can literature promote identification with the suffering of others and an empathetic connection between readers and fictional characters? Can this sentiment of sympathy translate into social solidarity and have political consequences? In this interview, professor and historian Lynn Hunt discusses the interplay between literature and human rights and reflects on our relationship to history, the fragility of democracy, and the self and society duality.